2020
DOI: 10.1097/aud.0000000000000986
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Hearing Aid Use and Hearing Aid Management Challenges in Infants

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
5
1
Order By: Relevance
“…Overall, better detection rates were observed for MF than HF stimuli, so an absent response at HF may be less informative than an absent response at MF. Demonstrating aided CAEP responses may be a useful tool to encourage caregivers to persist with infant hearing aid use, which can often be challenging (e.g., Walker et al 2013 ; Muñoz et al 2015 ; Caballero et al 2017 ; Muñoz et al 2019 ; Visram et al 2021 ). Using CAEP results to inform hearing aid adjustments should be just one tool, and a decision to adjust gain should be made in conjunction with the full clinical picture, understanding the possibility of false negative CAEP results, especially for HF.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, better detection rates were observed for MF than HF stimuli, so an absent response at HF may be less informative than an absent response at MF. Demonstrating aided CAEP responses may be a useful tool to encourage caregivers to persist with infant hearing aid use, which can often be challenging (e.g., Walker et al 2013 ; Muñoz et al 2015 ; Caballero et al 2017 ; Muñoz et al 2019 ; Visram et al 2021 ). Using CAEP results to inform hearing aid adjustments should be just one tool, and a decision to adjust gain should be made in conjunction with the full clinical picture, understanding the possibility of false negative CAEP results, especially for HF.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire evaluating the parents’ knowledge of hearing aid use revealed that better parental knowledge were associated with an improvement in subjective auditory performance. There are no resources available where parents can easily find sufficient information on hearing aid use and care after diagnosis and intervention ( 15 , 16 , 29 , 30 ). In studies, parents stated that they removed the hearing aids when outside of their home because of concerns about losing the hearing aid ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Small sample sizes, difficulties in accessing data and participant recruitment from mostly white, educated and higher income families also limit this. Much of the literature which explores parent-reported challenges to optimal hearing aid use focuses on situational and practical aspects of daily use [13,14] but often fails to capture cultural, linguistic and social barriers. A study which looked at hearing aid usage and challenges among children from Hispanic families, with many parents of lower income and education status within their participant group, discovered that 66% wore their hearing aids all day on 'good days'.…”
Section: Introductionmentioning
confidence: 99%